Changes in productivity in the virgin olive oil sector: An application to Protected Designations of Origin in Spain - Aparicio, Juan; Monge, Juan F.; Ortiz, Lidia; Pastor, Jesus T. (Spanish Journal of Agricultural Research, 2016)
Virgin olive oil is a key ingredient of the renowned Mediterranean diet. In this context, the main objective of this study was to estimate and decompose productivity change for Protected Designations of Origin (PDOs) in the Spanish virgin olive oil sector for the period 2008-2013. To this end, we introduced a Luenberger-type indicator based on a specific weighted additive model in Data Envelopment Analysis (DEA), which, in contrast to previous studies, captured all sources of inefficiency and avoided infeasibilities. Regarding the results, we found a reduction in productivity, in average terms, in the first periods analyzed (-0.12 and -1.65), followed by an improvement (0.79 and 0.54), that in the last period analyzed (2012-2013), however, returned to adverse figures (-0.47). In Spain, where foreign competition is weak, the most productive PDOs were those with an important number of oil mills and packaging/marketing companies such as “Montes de Toledo” and “Siurana”; productivity changes were mainly the consequence of downwards and upwards of the frontier of the technology over time. These changes were explained, to a certain extent, by the evolution of the economic crisis; and the productivity of the sector declined, in general, from 2008 to 2010, improving thereafter except for the last registered period, 2012-2013, where expectations for market recovery exceeded actual sales.